Can Ancient Science And Wisdom Of Yagya Therapy 'With Herbs Having Immune Boosting and Antiviral Properties' Aid In The Fight Against COVID19? - Ruchi Singh (Dr. Chinmay Pandya, 2020)
In the COVID19 pandemic, there is strong need of immune boosting and mental health approaches which are easily available and traditionally used for preventing as well as managing COVID19 infection. Since past 40 years, Dev Sanskriti University (DSVV) and parent institution (All World Gayatri Pariwar) has been working on various aspects of traditional herbal utility and Yagya Therapy. Vedic texts mentioned use of herbal fumes for health benefits as well as purifying air and removing seasonal pathogens from air through Bheshaj Yajnas (Yagya / Hawan). Bheshaj Yajna (herbal fumigation) was widely used in India to combat seasonal epidemics; scriptures described them in details. Studies have shown Yagya Therapy and herbal fumigation effects in various diseases i,e, common diseases such as diabetes, thyroid, as well as life threatening diseases such as cancer, multi-drug-resistant tuberculosis and in psychological ailments such as Obsessive-Compulsive Disorder and PolyCystic Ovarian Disease, epilepsy, depression, etc., indicating potential of herbal fumes for boosting immunity and aiding psychological wellbeing; besides, the herbal fumes is made using herbs known for their immune boosting and mental health care potential in Ayurveda and traditional knowledge. Hence, the study narrated the selective herbs which are pan-available and widely used traditionally in Yagya Therapy or generating herbal fumes, which can help boosting immunity and aid psychological wellbeing.